Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Siswa Pada Pembelajaran Pendidikan Agama Islam Kelas XI SMKN 2 Bukittinggi Tahun Ajaran 2021/2022 - Ulvia Risa; Zulfani Sesmiarni; Muhiddinur Kamal; Wedra Aprison (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The main problem in this paper is the unsatisfactory student learning outcomes caused by several factors, namely factors from within the students themselves, namely student interest, attention, talent and student IQ and factors from outside the student's self, namely environmental factors. This is evidenced by the lack of students' understanding of historical material about Islam in the modern era (1800-present). In addition, learning activities often only store event names, chronologies, years, and character names. Therefore it is hoped that the use of audio-visual learning media can arouse students' interest and not be boring. The purpose of this research is to find out how the learning outcomes are using audio-visual media in learning Islamic Religious Education Class XI SMKN 2 Bukittinggi. With the research hypothesis, Ha: learning outcomes with audiovisual media are better than learning outcomes without audiovisual media and Ho learning outcomes with audiovisual media are worse than learning outcomes without audiovisual media. Experimental design with group pre-test post-test design. Population and sample class XI. One class was selected as a random sample, namely class XI Boga 3 as the research object. Data collection techniques with testing. The sampling technique used is the sampling technique. Data analysis using statistical analysis. Class XI students of SMKN 2 Bukittinggi perform better when using audiovisual media, according to the author's research on the effect of audiovisual media on student learning outcomes on the topic of PAI. We can see this from the results of the analysis of the t-test (Paired Sample t-Test) with the final data obtained, namely t count = 8.926 > t table = 2.120 with a significant level α = 0.05, it can be concluded that the hypothesis Ha is accepted and Ho was rejected